S'étonner pour se professionnaliser : une expérience d'immersion sur le terrain en première année de formation d'ergothérapeutes - Dominique Broussal; Jean-Michel Caire; Sabrina Techene; Evelyne Castel-Lacanal; Xavier De Boissezon
This research studies the experimentation led from September 2016 to January 2017 in the Occupational therapy training Institute in Toulouse. It consisted in sending first-year students in immersion in physical therapy and rehabilitation services. Health-care professionals would present their activity and the students for their part, could observe situations of care and exchange with the team. Students' feedback of their experience, encouraging the expression of their "astonishments", took the shape of individual questionnaires and debriefing sessions in small groups. The analysis highlights the determining role that immersion plays in the emergence of questioning and astonishment relative to the approach of the patient, disease, health-care professional activity, and the professionalisation process of students themselves.